Violence against children, adolescents and women: the outcome of cases assisted at a teaching hospital - Lorena Belentani; Ana Carolina Miranda Sartorelli; William Campo Meschial; Muriel Fernanda de Lima; Magda Lucia Félix de Oliveira (Universidade Federal de Santa Maria, 2012)
Objective: knowing the outcome of violence victims assistance at a teaching hospital, in the northwest of Parana (Brazil), in 2009. Method: exploratory- descriptive study, in which the Notification Forms, the Individual Forms of Domestic, Sexual Violence and/or other kinds of Violence of 18 victims, filed in the hospital, were audited. Results: the forms belonged to women, victims of sexual violence (72.3%). All the biochemical examinations recommended were carried out; emergency contraception was conducted in six cases (33.3%) and 83.3% of the victims were advised to have laboratory monitoring, but at the first return, 53.3% of the victims had abandoned it. No register of communication networks between the hospital and the health care was found. Conclusion: studies concerning the assistance that violence victims receive in health service units should be stimulated, for more specific prevention actions and for improving the way victims are treated at health service units